Influence of enamel matrix derivative (Emdogain((R))) and sodium fluoride on the healing process in delayed tooth replantation: histologic and histometric analysis in rats - Poi, Wilson Roberto [UNESP]; Carvalho, Roberta Martinelli; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP]; Manfrin, Thais Mara; Rodrigues, Thais da Silveira (Blackwell Publishing, 2007)
Although it has already been shown that enamel matrix derivative (Emdogain((R))) promotes periodontal regeneration in the treatment of intrabony periodontal defects, there is little information concerning its regenerative capacity in cases of delayed tooth replantation. To evaluate the alterations in the periodontal healing of replanted teeth after use of Emdogain((R)), the central incisors of 24 Wistar rats (Rattus norvegicus albinus) were extracted and left on the bench for 6 h. Thereafter, the dental papilla and the enamel organ of each tooth were sectioned for pulp removal by a retrograde way and the canal was irrigated with 1% sodium hypochlorite. The teeth were assigned to two groups:in group I, root surface was treated with 1% sodium hypochlorite for 10 min (changing the solution every 5 min), rinsed with saline for 10 min and immersed in 2% acidulated-phosphate sodium fluoride for 10 min; in group II, root surfaces were treated in the same way as described above, except for the application of Emdogain((R)) instead of sodium fluoride. The teeth were filled with calcium hydroxide (in group II right before Emdogain((R)) was applied) and replanted. All animals received antibiotic therapy. The rats were killed by anesthetic overdose 10 and 60 days after replantation. The pieces containing the replanted teeth were removed, fixated, decalcified and paraffin-embedded. Semi-serial 6-mu m-thick sections were obtained and stained with hematoxylin and eosin for histologic and histometric analyses. The use of 2% acidulated-phosphate sodium fluoride provided more areas of replacement resorption. The use of Emdogain((R)) resulted in more areas of ankylosis and was therefore not able to avoid dentoalveolar ankylosis. It may be concluded that neither 2% acidulated-phosphate sodium fluoride nor Emdogain((R)) were able to prevent root resorption in delayed tooth replantation in rats.
Keywords: tooth replantation; dental enamel proteins; enamel matrix derivate; sodium fluoride